2018
DOI: 10.1590/s0100-83582018360100138
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Antioxidant Enzymes in Euphorbia heterophylla Biotypes and their Relation to Cross Resistance to ALS and Protox Inhibitors

Abstract: The characteristics of multiple resistance in Euphorbia heterophylla biotypes to herbicides that are inhibitors of ALS (Acetolactate synthase) and PPO (Protoporphyrinogen oxidase) and their responsible mechanisms are still not completely elucidated. The objectives of this study were to identify cross-resistance to herbicides from different chemical groups of ALS inhibitors (imidazolinones, sulfonylureas, pyrimidyl benzoates and sulfonanilides) and also PPO inhibitors (diphenylethers, phthalamides, oxadiazoles,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…For flumioxazin, differences in GR 50 parameters between the two populations were not significant, and thus resistance to flumioxazin was not confirmed in R PPO (Table 1). These results are consistent with other PPO-resistant E. heterophylla populations from Brazil (Trezzi et al 2005(Trezzi et al , 2006Xavier et al 2018). Trezzi et al (2005) studied two populations with high RF to fomesafen (39-and 62-fold) that were controlled with sulfentrazone (600 g ha −1 ) and flumioxazin (50 g ha −1 ) PRE.…”
Section: Cross-resistance To Ppo Inhibitors In Euphorbia Heterophyllasupporting
confidence: 87%
See 1 more Smart Citation
“…For flumioxazin, differences in GR 50 parameters between the two populations were not significant, and thus resistance to flumioxazin was not confirmed in R PPO (Table 1). These results are consistent with other PPO-resistant E. heterophylla populations from Brazil (Trezzi et al 2005(Trezzi et al , 2006Xavier et al 2018). Trezzi et al (2005) studied two populations with high RF to fomesafen (39-and 62-fold) that were controlled with sulfentrazone (600 g ha −1 ) and flumioxazin (50 g ha −1 ) PRE.…”
Section: Cross-resistance To Ppo Inhibitors In Euphorbia Heterophyllasupporting
confidence: 87%
“…Trezzi et al (2005) studied two populations with high RF to fomesafen (39-and 62-fold) that were controlled with sulfentrazone (600 g ha −1 ) and flumioxazin (50 g ha −1 ) PRE. In a E. heterophylla population from Virotino city, the RF was 15.1-fold for saflufenacil and 4.9-fold for flumiclorac (same chemical group as flumioxazin) (Xavier et al 2018). Regardless of the conditions adopted by different laboratories, the resistance levels and crossresistance patterns primarily depend on the population and its resistance mechanism.…”
Section: Cross-resistance To Ppo Inhibitors In Euphorbia Heterophyllamentioning
confidence: 99%
“…Mechanisms that confer tolerance to PPO inhibitors include: the reduction of absorption and translocation (Kilink et al 2011), the increased activity of antioxidant enzymes (Xavier et al 2018), and the rapid herbicide metabolism (Dayan et al 1997;Kilink et al 2011). In pre-emergence application, specific mechanisms capable of interfering with the absorption, translocation and metabolism of herbicidal compounds in plant tissues may contribute to increasing plant tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…4) and the characteristics of the commercial group, growth habit, and cycle (Table 1). Among the mechanisms considered important for the tolerance of plants to PPO inhibitors are the metabolism of herbicides to less toxic compounds (Dayan et al 1997;Kilink et al 2011), the antioxidative enzyme activity (Xavier et al 2018), and the herbicide absorption and translocation differences (Kilink et al 2011). Probably the mechanisms of tolerance to PPO--inhibiting herbicides mentioned above are not associated with specific morphophysiological characteristics or the center of origin of bean cultivars.…”
Section: Discussionmentioning
confidence: 99%

Journal of Plant Protection Research

Brusamarello,
Trezzi,
Pagnoncelli Júnior
et al. 2021
“…Thus, their inhibition could be helpful to counteract these serious pathological disorders [24]. Previous studies have shown that several members of the genus Euphorbia have shown inhibitory activities against a wide range of enzymes, and have proven their potential as a potent enzyme inhibitory therapeutic agent to be used in wide variety of diseases [25,26]. Because of these reasons, the present study was designed to assess phenolic, flavonoid content, in-vitro radical scavenging, and enzyme inhibitory potential of EN using different chemical and biochemical enzymes assays.…”
Section: Introductionmentioning
confidence: 99%